Arbuscular Mycorrhizal Fungi (Glomus mosseae) Improves Growth, Photosynthesis and Protects Photosystem II in Leaves of Lolium perenne L. in Cadmium Contaminated Soil - Zhang, Huihui; Xu, Nan; Li, Xin; Long, Jinghong; Sui, Xin; Wu, Yining; Li, Jinbo; Wang, Jifeng; Zhong, Haixiu; Sun, Guang Y. (Frontiers in Plant Science, 2018)
In this study, the effects of inoculating arbuscular mycorrhizal fungi (Glomus mosseae) on the growth, chlorophyll content, photosynthetic gas exchange parameters, and chlorophyll fluorescence characteristics of Lolium perenne L. in cadmium (Cd) contaminated soil were investigated. The results showed that the root vigor of L. perenne declined, while the chlorophyll content significantly decreased with the increase of Cd content, especially the chlorophyll a content in leaves. The photosynthetic carbon assimilation capacity and PSII activity of L. perenne leaves were also significantly inhibited by Cd stress, especially the electron transfer at the receptor side of PSII, which was more sensitive to Cd stress. The infection level of G. mosseae on L. perenne roots was relatively high and inoculation with G. mosseae increased the mycorrhizal infection rate of L. perenne roots up to 50–70%. Due to the impact of the mycorrhizal infection, the Cd content in L. perenne roots was significantly increased compared to non-inoculated treatment; however, the Cd content in the aboveground part of L. perenne was not significantly different compared to the non-inoculated treatment. After inoculation with G. mosseae, the root vigor of L. perenne increased to some extent, alleviating the chlorophyll degradation in L. perenne leaves under Cd contaminated soil. Infection with G. mosseae can improve the stoma limitation of L. perenne leaves in Cd contaminated soil and increase the non-stomatal factors including the tolerance of its photosynthetic apparatus to Cd, to improve photosynthetic capacity. G. mosseae infection can improve the photosynthetic electron transport capacity of PSII in L. perenne leaves under Cd stress and promotes the activity of the oxygen-evolving complex to different degrees at the donor side of PSII and the electron transport capacity from QA to QB on the receptor side of PSII. Thus, this guarantees that L. perenne leaves inoculated with G. mosseae in Cd contaminated soil have relatively higher PSII activity. Therefore, inoculation with G. mosseae can improve the capacity of Cd tolerance of L. perenne with regard to various aspects, such as morphological characteristics and photosynthetic functions, and reduce the toxicity of Cd on L. perenne.